PENGARUH KINERJA APARATUR PEMERINTAH DAERAH, PENGELOLAAN KEUANGAN DAERAH, SISTEM PENGENDALIAN INTERNAL, DAN IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAH TERHADAP PENERAPAN GOOD GOVERNANCE - Siti Indah Dhiyavani; Azwir Nasir; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aims to examine the influence local government officials performance, local financial management, internal control system, and government accounting standard implementation to the good governance implementation. Object of this research is local government unit at medium region Pekanbaru. Every each local government unit, this research only need three respondents. There are one hundred twentynine questionnaires were sent, but only ninety questionnaires are returned. That data are analyzed by multiple regression method. The variables were examined are influence oflocal government officials performance, local financial management, internal control system, and government accounting standard implementation to the good governance implementation. The results of this research showed that local government officials performance has an effect to the good governance implementation with 0,045 significant value, local financial management has an effect to the good governance with 0,04 significant value, and government accounting standard implementation variable has an effect to the good governance implementation with 0,000 significant value. Butinternal control systemvariable has not an effect to the good governance implementation with te counting table 0,151. The coefficient determinant of this result showed that only 62,8% independent variables can examined the dependent variable and 37,2% from other independent variable.Keywords : Local Government Officials Performance, Financial Management,Internal Control System, Government Accounting Standard, and Good Governance Implementation